INTEGRATIVE APPROACH TO TEACHING CARDIOLOGY: ISSUES OF RELATIONSHIP WITH OTHER SPHERES OF MEDICINE - Kenjayev M. L.; Berdiyeva Zuhra; Abdunazarova Fotima (Bright Mind Publishing, 2025)
This article explores the methodological and practical foundations of teaching cardiology through an integrative approach in connection with other medical fields. Teaching cardiology in relation to endocrinology, neurology, nephrology, and pharmacology plays a significant role in developing students’ systematic and professional thinking. The article highlights the advantages of the integrative method, its practical application, and outcomes based on students’ feedback.
Keywords: Cardiology, integrative approach, medical education, interdisciplinary connection, student feedback, clinical knowledge.